PENERAPAN DAN IMPLEMENTASI SISTEM PAKAR DALAM MENDEKTEKSI GEJALA PENYAKIT EPILEPSI - ADHI SUSANO (Faktor Exacta, 2016)
By progressing of technology, it will help for making an application to detect some sympomts of epilepsi. The epilepsi is generally in all stage of age, baby, kids, adolescent, adult and old people. Epilepsi can be happened because of there is distraction of neuro in cerebelum so it will make awareness, emotion, halusination, convultions, and painful in head. By applying and implementing expert system is being an application that can diagnose epilepsi, so the doctors can diagnose faster, easier and efective. Beside that the expert system si usefull to replace human by using the computer program, it also help doctors to check their patient and the benefit of this system is really needed. Keywords: expert system, Neurology, Epilepsy